The Structured Discharge Planning Toward Patient's Readiness in Performing Colostomy Care - Nurleli Nurleli; Roma Sitio; Rapitos Sidiq (University of Muhammadiyah Malang, 2021)
Introduction: Colostomy patients face major changes in various aspects that occur due to lack of knowledge, preoperative preparation, and postoperative management. In addition, the implementation of discharge planning was generally in the form of a patient resume but does not evaluate the ability of patients and families to perform colostomy care independently. Objectives: This study aims to determine the effectiveness of structured discharge planning on the readiness of patients undergoing colostomy care. Methods: The descriptive-analytic study quasi-experimental approach post-test only with control group was designed to determine the effectiveness of structured discharge planning towards patient’s readiness in performing colostomy care. Data collection was carried out for 20 colostomy patients selected accidentally. Data analysis was performed by independent t-test. Results: The result found that patient’s readiness in performing colostomy care was significantly increased in the intervention group (p-value 0.008). Conclusion: The structured discharge planning which has been prepared at the beginning of the patient's hospitalization for colostomy patients’ regarding stoma care was highly needed to optimize the ostomate in carrying out colostomy care independently.